As pesquisas em educação em ciências na interface com a educação indigena: a abordagem qualitativa na evidência dos dados - OLIVEIRA, Lúcia Helena Soares de (Universidade Federal de Mato Grosso, 2022)
In this paper we discuss the methodological paradigms used in the last ten years in research in Education in Science and Indigenous Education. We approached the survey carried out in the databases of the Portals of Capes, BDTD and Google Scholar. The study is part of the theoretical basis of a research that is underway within the scope of the Post-Graduate Program in Science and Mathematics Education -REAMEC, by the Federal University of Mato Grosso do Sul, umbrella. This study has a bibliographic character and is supported in the research through surveys carried out in articles, Theses, Dissertations and works of specialists that approach the subject in question. Thus, the studies reflect that the qualitative approach allows the detailed understanding of the meanings and the situational characteristics of the subjects involved, is concerned with a reality that can not be quantified or reduced to the operationalization of variables, emphasizing that the purpose of the scientific research does not is centered only on the presentation of a report or description of the data, but on the report of the interpretative development of the data obtained.